The vulnerabilities of lives: Zika, women and children in Alagoas State, Brazil - Ambrogi, Ilana G. (Cad Saude Publica, 2021)
Until 2015, Zika was mostly unknown in Brazil and in the world. Since then, the Zika virus has been found to be vertically transmitted and to cause congenital Zika syndrome (CZS). This study aims to describe and analyze the vulnerabilities of the women and children most affected by the Zika epidemic in Brazil. Alagoas has the lowest Human Development Index in Brazil and one of the highest rates of adolescent pregnancy. Between December 2016 and March 2017, interviews were conducted with 54 women with children affected by Zika. The interviews had two components: a narrative-oriented conversation and a semi-structured questionnaire. This comprehensive mixed methods case study represented 45% of the confirmed CZS cases and 20% of the cases under investigation in the state at that time. The women are predominantly Afro-Brazilian; most experienced their first pregnancy during adolescence, and had little education. Many were not covered by social protection programs and were not receiving adequate health care. The rights and needs of these women and children are impacted by a systemic lack of access to services and medications. There is inadequate transportation to services that many families depend on. Discrimination against their children with disabilities is a new and complex concept in their lives. The Zika epidemic has compounded rights violations in their lives and worsened their social and economic layers of vulnerability. There is an urgent need for a robust public response to guarantee the rights of these women and children and to implement mechanisms to prevent and eliminate their vulnerabilities.